Effectiveness Government Budgeting Preparation for Regional Development Post COVID-19: Evidence from South Sulawesi Province, Indonesia - Andi Nurmalasari; Sylvia Sylvia; M. Salim Sultan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to analyze the effect of regional apparatus coordination and human resource capacity on the organizational commitment required to prepare the Regional Revenue and Expenditure Budget (APBD). This study was conducted at the Office of the Regional Research and Development Planning Agency of the Province of South Sulawesi. This study employs a quantitative strategy and survey methodology. In this study, 97 employees were selected through a non-probability sampling technique. Validation of data includes testing research instruments for validity and reliability and testing for classical assumptions and hypotheses. The analysis of data involved descriptive and inferential analysis—testing hypotheses with path analysis by examining direct and indirect effects. The t-test with a 5% tolerance determines the immediate impact, whereas the Sobel test determines the indirect impact. The study results indicate that direct coordination of regional apparatus, human resource capacity, and organizational commitment positively and significantly affect preparing the APBD. In contrast, indirect coordination of regional apparatus, human resource capacity, and organizational commitment has a positive and significant effect on the practice of the APBD. Regional apparatus coordination has the highest contribution between human resource capacity and organizational commitment, so prioritizing regional apparatus coordination will improve the optimization of APBD preparation. We recommend that the employees of the Regional Research and Development Planning Agency of the Province of South Sulawesi enhance consistency in the preparation of activities to encourage the participation of all relevant parties in the ongoing monitoring of work stages. Leaders should focus on the level of work mastery of their employees by enhancing their technical knowledge through seminars, training, etc. so that their work objectives are more quantifiable. Consistently increasing employee awareness of personal and organizational goals enables employees to contribute optimally to achieving personal and organizational objectives.